Sex Differences in Correlation with Gene Expression Levels between Ifi200 Family Genes and Four Sets of Immune Disease-Relevant Genes - Yanhong Cao; Lishi Wang; Cong-Yi Wang; Jicheng Ye; Ying Wang; Tiantian Li; Franklin Garcia-Godoy; Dianjun Sun; Weikuan Gu; Arnold E. Postlethwaite (Journal of Immunology Research)
Background. The HIN-200 family genes in humans have been linked to several autoimmune diseases—particularly to systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Recently, its human counterpart gene cluster, the Ifi200 family in mice, has been linked to spontaneous arthritis disease (SAD). However, many immune-mediated diseases (including RA and SLE) show gender difference. Understanding whether or not and how these genes play a role in sex difference in immune-mediated diseases is essential for diagnosis/treatment. Methods. This study takes advantage of the whole genome gene expression profiles of recombinant inbred (RI) strain populations from female and male mice to analyze potential sex differences in a variety of genes in disease pathways. Expression levels and regulatory QTL of Ifi200 family genes between female and male mice were first examined in a large mouse population, including RI strains derived from C57BL/6J, DBA/2J (BXD), and classic inbred strains. Sex similarities and differences were then analyzed for correlations with gene expression levels between genes in the Ifi200 family and four selected gene sets: known immune Ifi200 pathway-related genes, lupus-relevant genes, osteoarthritis- (OA-) and RA-relevant genes, and sex hormone-related genes. Results. The expression level of Ifi202b showed the most sex difference in correlation with known immune-related genes (the P value for Ifi202b is 0.0004). Ifi202b also showed gender difference in correlation with selected sex hormone genes, with a P value of 0.0243. When comparing coexpression levels between Ifi200 genes and lupus-relevant genes, Ifi203 and Ifi205 showed significant sex difference (P values: 0.0303 and 0.002, resp.). Furthermore, several key genes (e.g., Csf1r, Ifnb1, IL-20, IL-22, IL-24, Jhdm1d, Csf1r, Ifnb1, IL-20, IL-22, IL-24, and Tgfb2 that regulate sex differences in immune diseases) were discovered. Conclusions. Different genes in the Ifi200 family play different roles in sex difference among dissimilar pathways of these four gene groups.